Virtual Reality dalam Menurunkan Kecemasan dan Ketakutan pada Anak Usia Sekolah dan Remaja yang Dirawat - Enjelita Karujan; Dessie Wanda; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the effect of virtual reality on the anxiety and fear of school-age children and adolescents when receiving treatment at the hospital. The method used is a systematic review of nine searched articles through the Proquest, Science Direct, Scopus, Pubmed, and Springer Link databases, and through hand searching, with article inclusion criteria using virtual reality interventions involving school-age children and adolescents in hospital settings, published between 2013-2022 in English and Indonesian, can be accessed in full text. The results of the study show that the use of virtual reality can reduce anxiety and fear in school-age children and adolescents who are hospitalized. In conclusion, distraction using virtual reality effectively reduces stress and worry in school-age children and adolescents who are hospitalized, so it can be the intervention of choice for nurses in providing nursing care to manage anxiety and fear. Keywords: Children, Anxiety, Fear, Hospitals, Virtual Reality